A novel h-BN–RGO hybrids for epoxy resin composites achieving enhanced high thermal conductivity and energy density. Issue 38 (27th April 2017) - Huang, Tao; Zeng, Xiaoliang; Yao, Yimin; Sun, Rong; Meng, Fanling; Xu, Jianbin; Wong, Chingping
Abstract : In recent decades, significant attention has been focused on developing composite materials with high thermal conductivity utilizing h-BN, which has outstanding thermal conductivity. Abstract : In recent decades, significant attention has been focused on developing composite materials with high thermal conductivity utilizing h-BN, which has outstanding thermal conductivity. However, the enhancement in thermal conductivity by using h-BN is commonly limited because of high thermal resistance between h-BN and polymer materials. Herein, we fabricated novel h-BN–RGO hybrids (h-BN–RGO), by electrostatic assembly between h-BN and GO. It is found that the addition of h-BN–RGO hybrids into epoxy resins can enhance the thermal conductivity. The samples containing 26.04 vol% h-BN–RGO exhibit the highest thermal conductivity (3.45 W m −1 K −1 ), which is as high as 16 times that of neat epoxy resin (0.24 W m −1 K −1 ). The epoxy resins/h-BN–RGO composites also exhibit an enhanced dielectric constant (11.12) and low loss tangents (0.05). The energy density of the composites reaches 0.51 J cm −3 in the composites with 26.04 vol%, which is 79.6% higher than that of the pure epoxy. We attribute the enhanced thermal conductivity to the well-designed h-BN–RGO interface as well as the good dispersion of BN–RGO hybrids in epoxy resin. The energy density is mainly due to the absorbed effect of RGO nanosheets at the BN surface and its good dispersion in comparison with pure BN. This work offers a new insight into the methods for the improvement of thermal conductivity and energy storage characteristics, which has potential applications in integrated circuit packaging and structural energy storage.